2022
DOI: 10.3389/fendo.2022.897776
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of glucose-lowering drugs in children and adolescents with type 2 diabetes: A systematic review and network meta-analysis

Abstract: ObjectiveType 2 diabetes is more common in adults, but is becoming the major concern in children and adolescent recently. This study aimed to provide additional pharmaceutical management for children and adolescents with type 2 diabetes by assessing the efficacy and safety of several glucose-lowering drugs.MethodsSearches were performed in PubMed, Medline, Ovid, Cochrane Controlled Register of Trials (CENTRAL), and ClinicalTrials.gov that reported the efficacy and safety of drugs for children and adolescents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Although DPP-4is are not approved for use in the pediatric population, a recent study conducted in youths (aged 10-17 years) with type 2 diabetes found that sitagliptin was generally well tolerated and had a safety profile similar to that reported in adults (48). Safety of DPP-4is for the treatment of type 2 diabetes in children and adolescents was also confirmed in a recent meta-analysis (49).…”
Section: Discussionmentioning
confidence: 81%
“…Although DPP-4is are not approved for use in the pediatric population, a recent study conducted in youths (aged 10-17 years) with type 2 diabetes found that sitagliptin was generally well tolerated and had a safety profile similar to that reported in adults (48). Safety of DPP-4is for the treatment of type 2 diabetes in children and adolescents was also confirmed in a recent meta-analysis (49).…”
Section: Discussionmentioning
confidence: 81%
“…An exponential increase in the prevalence of obesity among adults and kids following the coronavirus disease 2019 (COVID 19) pandemic has contributed to the increased prevalence of T2DM in children. A network meta-analysis published in 2022 highlighted that metformin, saxagliptin, linagliptin, exenatide, liraglutide and dapagliflozin have been evaluated in different clinical trials in children with T2DM and advocated for the use of the saxagliptin metformin combination to treat T2DM in children [ 27 ]. Saxagliptin use has decreased significantly in adults with T2DM following the issue of a black box warning for heart failure [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A network meta-analysis published in 2022 highlighted that metformin, saxagliptin, linagliptin, exenatide, liraglutide and dapagliflozin have been evaluated in different clinical trials in children with T2DM and advocated for the use of the saxagliptin metformin combination to treat T2DM in children. 27) Saxagliptin use has decreased significantly in adults with T2DM following the issue of a black box warning for heart failure. 28) Since then, many more studies have been published on oral antidiabetes medication use in children, especially SGLT2i like empagliflozin.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of the efficacy and safety of several glucose-lowering medications provides additional options for YODM management. Compared to FDA-approved drugs, dapagliflozin, sitagliptin+metformin, and saxagliptin+metformin showed better efficacy, indicating the top ten treatment methods for YODM in individuals aged 10–17: saxagliptin+metformin, liraglutide+metformin, liraglutide, dapagliflozin, exenatide-2 mcg, sitagliptin+metformin, linagliptin-5 mg, linagliptin-1 mg, metformin, and exenatide-5/10 mcg ( 149 ).…”
Section: Comprehensive Management Strategies For Yodm From the Perspe...mentioning
confidence: 99%